Brigham Young - Mason, David V. (David Vaughn), author.
1 online resource (xiii, 184 pages)
Keywords: "Brigham Young was one of the most influential--and controversial--Mormon leaders in American history. An early follower of the new religion, he led the cross-continental migration of the Mormon people from Illinois to Utah, where he built a vast religious empire that was both revolutionary and authoritarian, radically different from yet informed by the existing culture of the U.S. In a lively, concise narrative bolstered by primary documents, and supplemented by a robust companion website, David Mason tells the dynamic story of Brigham Young, and in the process, illuminates the history of the LDS Church, religion in America, and the development of the American west"--